NATURE VS. NURTURE IN ALBUQUERQUE: WHAT BREAKING BAD AND BETTER CALL SAUL TEACH US ABOUT HOW WE TALK ABOUT CRIMINALS - Romanowski, Max (Dialogue, 6(2), 2019)
Breaking Bad and Better Call Saul focus on the criminal transformation of their two main characters, Walter White (Bryan Cranston) and Jimmy McGill (Bob Odenkirk). While quite similar on the surface, Walter and Jimmy’s narratives represent two different criminal transitions, evoking the classic nature vs nurture conversation. Both of these shows bring the conversation to the idea of inevitability. The nature vs. nurture argument is a popular one because it acts as a teaching tool for how we think and talk about criminal behavior. At first, it follows that since criminality was in Walter White’s nature the whole time, his transition should feel the most inevitable, with the inverse being true of Jimmy. However, since Better Call Saul is a prequel to Breaking Bad, the opposite ends up happening. Even though Jimmy may only need the right people around him to be saved from his descent, his presence as Saul Goodman on Breaking Bad reminds the audience that it is Jimmy who is already fated to become a criminal. This dichotomy highlights the distinctive pedagogical opportunity present in both of these shows. Through their subversion of the concepts of nature and nurture, they allow for a unique teaching opportunity regarding how we talk about criminals. This article explores what they teach us and how their commentary can be used as a pedagogical tool for learning about criminal behavior in more nuanced ways. Keywords: Breaking Bad, Better Call Saul, Nature, Nurture, Social Learning Theory, Classical Conditioning
Keywords: Type of access: Open Access